2000
DOI: 10.1136/heart.84.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac pressures in the human fetus

Abstract: Objective-To obtain normal values for intracardiac pressures in the human fetus. Design-Intracardiac pressures were measured directly in the four chambers of the human fetal heart during clinically indicated invasive obstetric procedures. Setting-Department of fetal medicine in a tertiary referral centre. Patients-39 fetuses between 16 and 29 weeks of gestation. Results-The ventricular waveforms obtained were similar to those found in postnatal life. There was an increase in ventricular systolic and end diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
3
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 25 publications
(10 reference statements)
8
79
3
6
Order By: Relevance
“…Thus, fetal semilunar valves and the aorta and pulmonary trunk are subjected to equal pressures, which progressively increase during gestation. 21 The present study revealed that fetal, second-trimester semilunar (aortic and pulmonary) valves lacked distinguishable layers, were composed primarily of proteoglycans, had no detectable elastin, had small amounts of disorganized collagen, and were histologically identical (likely because of a similar physiological environment during development 22 ). Valvular ECM elements accommodate repetitive shape and dimension changes throughout the cardiac cycle and must adapt to different mechanical stresses throughout life.…”
Section: Semilunar Valve Architecture Changes Throughout Development mentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, fetal semilunar valves and the aorta and pulmonary trunk are subjected to equal pressures, which progressively increase during gestation. 21 The present study revealed that fetal, second-trimester semilunar (aortic and pulmonary) valves lacked distinguishable layers, were composed primarily of proteoglycans, had no detectable elastin, had small amounts of disorganized collagen, and were histologically identical (likely because of a similar physiological environment during development 22 ). Valvular ECM elements accommodate repetitive shape and dimension changes throughout the cardiac cycle and must adapt to different mechanical stresses throughout life.…”
Section: Semilunar Valve Architecture Changes Throughout Development mentioning
confidence: 91%
“…21 These hemodynamic changes were associated with decreased VIC activation in late neonatal (1 to 30 days of survival) pulmonary valves (6.3Ϯ0.8%; nϭ5), whereas aortic valve VICs remained activated (20.5Ϯ2.2%, nϭ5; PϽ0.05; Figure 4). Nevertheless, this change did not occur immediately, because the numbers of activated VICs in early neonatal valves with minutes to hours of survival were identical in both pulmonary (20.5%; nϭ5) and aortic valves (20.5%; nϭ5).…”
Section: Fetal Valves Contain Activated Cells That Overexpress Proteomentioning
confidence: 99%
“…• Two ventricular pumps perfuse the same systemic circulation in a parallel fashion with the right ventricular output being greater than the left 22 .…”
Section: Changes In the Fetal Heart In Iugrmentioning
confidence: 99%
“…However, the timing of these changes during development and the mechanisms regulating them are incompletely understood (10,26,30,44,48). Furthermore, it is evident that this differs between and within various vascular beds (4,43,53,55).…”
mentioning
confidence: 99%